Outcome of Dapsone in the Treatment of Ashy Dermatosis - Hossain, MS; Bhuian, I; Wahab, A; Khan, SA (Journal of Shaheed Suhrawardy Medical College, 2012)
Background: Ashy dermatosis or Erythema Dyschromicum Perstans is a rare disorder of unknown etiology characterized by asymptomatic,slowly progressive, ashen-gray macular pigmentation of the skin. Various therapies have been tried without any benefit. The anti-inflammatory activity of dapsone on Erythema Dyschromicum Perstans may be the first oral treatment option. Objective: The aim of the present study was to evaluate the efficacy of dapsone in the treatment of ashy dermatosis. Methodology: This study was carried out on total thirty (30) cases having ashy dermatosis & age group 20-60 years were selected for the study of which 16 females & 14 males during the period of January 2010 to December 2011 in the Department of Dermatology & Venereology of Shaheed Suhrawardy Medical College Hospital and Bangabandhu Sheikh Mujib Medical University at Dhaka city of Bangladesh. All the cases were diagnosed clinically & confirmed by histopathological examination. The patients were given Dapsone 100 mg daily for three months & follow up was done for the next 3 months. Results: 16(53.33%) females & 14(46.66%) males were included in the study. Out of thirty patients, two patients (6.66%) shown excellent response, seven patients (23.33%) shown good response, eight (26.66%) patients shown fair response, 8 patients (26.66%) shown poor response & remaining five patients (16.66%) did not show any response clinically. So improvement was shown in 25(83.33%) cases and 5(16.66%) cases show no improvement at all. Conclusion: This study suggests that dapsone has significant efficacy profile for treatment option of ashy dermatosis. DOI: http://dx.doi.org/10.3329/jssmc.v4i1.11998 J Shaheed Suhrawardy Med Coll, 2012;4(1):18-21